Transient receptor potential ankyrin 1 ion channel expressed by the Edinger-Westphal nucleus contributes to stress adaptation in murine model of posttraumatic stress disorder - Konkoly, János; Kormos, Viktória; Gaszner, Balázs; Correia, Pedro; Berta, Gergely; Biró-Sütő, Tünde; Zelena, Dóra; Pintér, Erika (Frontiers in Cell and Developmental Biology, 2022)
The centrally projecting Edinger-Westphal nucleus (EWcp) is involved in stress adaptation. Transient receptor potential ankyrin 1 (TRPA1) mRNA was previously shown to be expressed abundantly in mouse and human EWcp urocortin 1 (UCN1) positive neurons and reacted to chronic stress. Since UCN1 neurons are deeply implicated in stress-related disorders, we hypothesized that TRPA1/UCN1 neurons are also affected in posttraumatic stress disorder (PTSD). We examined male Trpa1 wild-type (WT) and gene-deficient (KO) mice in the single prolonged stress (SPS) model of PTSD. Two weeks later the behavioral changes were monitored by forced swim test (FST) and restraint. The Trpa1 and Ucn1 mRNA expression and the UCN1 peptide content were assessed by RNAscope in situ hybridization technique combined with immunofluorescence labeling in the EWcp. SPS-induced immobility was lower in Trpa1 KO compared to WT animals, both in the FST and restraint, corresponding to diminished depression-like behavior. The copy number of Trpa1 mRNA decreased significantly in EWcp of WT animals in response to SPS. Higher basal Ucn1 mRNA expression was observed in the EWcp of KO animals, that was not affected by SPS exposure. EWcp neurons of WT animals responded to SPS with substantially increased amount of UCN1 peptide content compared to control animals, whereas such changes were not observable in KO mice. The decreased Trpa1 mRNA expression in the SPS model of PTSD associated with increased neuronal UCN1 peptide content suggests that this cation channel might be involved in the regulation of stress adaptation and may contribute to the pathomechanism of PTSD.